2006
DOI: 10.1007/s00192-006-0231-6
|View full text |Cite
|
Sign up to set email alerts
|

The tension-free vaginal tape in women with a non-hypermobile urethra and low maximum urethral closure pressure

Abstract: The objective of this study was to estimate the cure rate and to identify risk factors that predict failure of the tension-free vaginal tape (TVT) in women with stress urinary incontinence (SUI), a non-hypermobile urethra, and low maximum urethral closure pressure. Thirty-six women with SUI, a non-hypermobile urethra (straining urethral angle Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…Most studies of retropubic slings have shown that measures of VLPP and MUCP were not associated with surgical success rates. [1013] A recent metanalysis confirmed that urethral function did not predict outcome of MUS, regardless of approach. [14] In a randomized surgical trial of transobturator and retropubic MUS, Barber et al reported that VLPP, considered either as a continuous or dichotomous variable (<60 cm/H 2 O) was not associated with failure of either procedure after one year.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of retropubic slings have shown that measures of VLPP and MUCP were not associated with surgical success rates. [1013] A recent metanalysis confirmed that urethral function did not predict outcome of MUS, regardless of approach. [14] In a randomized surgical trial of transobturator and retropubic MUS, Barber et al reported that VLPP, considered either as a continuous or dichotomous variable (<60 cm/H 2 O) was not associated with failure of either procedure after one year.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective series of 174 patients undergoing distal to midurethral retropubic polypropylene Effectiveness of MUS in ISD and SUI Lim and Dwyer 429 slings, Rodriguez et al [30] found no significant differences in efficacy in patients with various different VLPP values. Table 1 shows a summary of studies investigating the outcome of TVT in an ISD setting [31][32][33][34][35][36][37][38]. Overall, it would appear that retropubically placed TVT are effective in treating women with both urinary stress incontinence (USI) and ISD, although with some studies showing slightly lower cure rates.…”
Section: Intrinsic Sphincter Deficiency and Midurethral Slingsmentioning
confidence: 93%
“…However, although these are statistical differences, the clinical significance is probably negligible, as the differences are small. If any clinical relevance should be assigned to these differences, it would be that this adds strength to the favourable outcome results for the participants, due to the fact that both a low MUCP (121) For the POSUI study (Paper III), we also wanted to test for selection bias (post study analysis). We did this by comparing study-women to other women having had POP surgery in the same time period at our Department, but who for some reason did not participate in the study.…”
Section: Study Design and Study Populationsmentioning
confidence: 99%